Urgensi Life Long Learning dalam Membangun Daya Saing Tenaga Kerja di Era Ekonomi Digital - Diana Zumrotus Sa’adah; Yudia Gusti Fitiyani; Lidya Agustina; Wulan Sumarni; Padilah Padilah; Noval Syabirin Rahmadan (Kajian Ekonomi dan Akuntansi Terapan, 2025)
The rapid development of the digital economy and technology transformation requires the workforce to possess adaptive and sustainable skills. Life Long Learning (LLL) has become an essential strategy to maintain relevance, competitiveness, and the sustainability of workforce competencies in the digital era. This article aims to conceptualize the urgency of LLL in enhancing workforce competitiveness amidst the challenges and opportunities of the digital economy. The method used is a literature study, analyzing various journals, scholarly articles, and relevant documents. The findings show that LLL not only improves technical competencies but also strengthens soft skills and fosters a growth mindset, which is crucial in facing technological changes. LLL also enables the workforce to continuously develop, adapt to changes, and seize opportunities in the digital economy. To create a sustainable learning ecosystem, proactive government policies, cross-sector collaboration, and a workplace culture that supports continuous learning are essential. Therefore, LLL is key in preparing a competitive workforce capable of innovating in the ever-evolving digital era.